Study on Plastic Deformation Zone of Titanium Alloy. (December 2019) - Guo, P; Zhao, Y.Q; Jia, G.Y; Hong, Q; Hou, H.M; Pan, H; Zhang, Y.Q; Liu, D.X
Abstract: During the crack propagation, crack tip contains stress odd singularity and has specific yield range. As the cycling loading continuing, the crack grows in the plastic zone. So the plastic zone is crucial to crack propagation action. In this paper, the crack propagation route was observed in different microstrctures, the deformation characteristic of plastic zone was analyzed for equiaxed structure and lamellar structure. The results show that crack propagation path is more straighter in equiaxed structure than that in lamellar structure. There were more tiny cracks near the crack surface in the lamellar structure during the crack growth, which shows that lamellar structure has a bigger plastic zone during the deformation.The plastic deformation need absorb the energy, which hinders the crack propagation.